Students as teachers: Design of a student-led course on sustainability education - Herranen, Jaana; Tolppanen, Sakari; Vesterinen, Veli-Matti; Aksela, Maija (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
Students’ role as active learners can be enhanced by giving the students more responsibility for their own learning. Could the students be suggesting the content and methods used in a class? Could the students be designing them? Or even, design the whole course and run it? These questions lead to a pilot course on student-led teacher education course on sustainable development in the chemistry teacher education unit, the University of Helsinki. This pilot course design, “Sustainable development in Education”, is presented in this chapter in the light of the initial ActSHEN-principles. The following chapter, ‘A student point of view’, is written from the perspective of the students, who planned and ran the pilot course.